Neuronal activity of the medulla oblongata revealed by manganese-enhanced magnetic resonance imaging in a rat model of gastroesophageal reflux-related cough - Chen, Z; Gu, D; Fan, L; Zhang, W; Sun, L; Chen, H; Dong, R; Lai, K (Physiological research, 2019)
We investigated neuronal activity of the medulla oblongata during gastroesophageal reflux-related cough (GERC). A rat model of GERC was generated by perfusing HCl into lower esophagus and inducing cough with citric acid. The HCl group rat was received HCl perfusion without citric acid-induced cough. The saline control rat was perfused with saline instead and cough was induced. Citric acid-induced cough rat was only induced by citric acid. Blank group rats were fed normally. Fos expressions were observed in medulla oblongata nuclei using immunohistochemistry. Manganese-enhanced magnetic resonance imaging (MEMRI) was performed to detect the Mn(2+) signal following intraperitoneal injection of MnCl(2). HCl perfusion and citric acid-induced cough caused Fos expressions in the nucleus of solitary tract (nTS), dorsal motor nucleus of the vagus (DMV), paratrigeminal nucleus (Pa5), and intermediate reticular nucleus (IRt), which was higher than HCl group, saline control group, citric acid-induced cough group, and blank group. A high Mn(2+) signal was also observed in most of these nuclei in model rats, compared with blank group animals. The Mn(2+) signal was also higher in the HCl, saline and citric acid-induced cough group animals, compared with blank group animals. The study showed medulla oblongata neurons were excited in a HCl perfusion and citric acid-induced cough rat model, and nTS, DMV, Pa5 and IRt neurons maybe involved in the cough process and signal integrate.
Keywords: modely nemocí na zvířatech; Male; Medulla Oblongata; potkani Sprague-Dawley; magnetická rezonanční tomografie; Manganese; medulla oblongata; mužské pohlaví; neurony; gastroezofageální reflux; krysa rodu Rattus; Cough; Animals; zvířata; Neurons; Rats; Disease Models, Animal; mangan; Magnetic Resonance Imaging; kašel; Gastroesophageal Reflux; Rats, Sprague-Dawley